Inherited disorders of the fibrinolytic pathway. (October 2019) - Jain, Shilpa; Acharya, Suchitra S.
Abstract: Deficiencies or excessive activation of the  fibrinolytic system can result in severe, lifelong bleeding disorders. The most severe clinical phenotype is caused by α2−Antiplasmin (α2−AP) deficiency which results in excess fibrinolysis due to the inability to inhibit plasmin. Another bleeding disorder due to a defect in the fibrinolytic pathway results from Plasminogen activator inhibitor-1 (PAI-1) deficiency causing enhanced fibrinolysis due to the decreased inhibition of plasminogen activators resulting in increased conversion of plasminogen to plasmin. Both these disorders are rare and have an autosomal recessive pattern of inheritance. They can remain undetected as routine coagulation and platelet function tests are normal. A unique gain-of-function defect in fibrinolysis causes the Quebec platelet disorder (QPD) which is characterized by profibrinolytic platelets containing increased urokinase-type plasminogen activator (uPA) in the α−granules. A high index of suspicion based on clinical phenotype along with the availability of specialized hemostasis testing is required for timely and accurate diagnosis. Antifibrinolytic agents, such as tranexamic acid or ε−aminocaproic acid, are the mainstays of treatment which inhibit fibrinolysis by preventing the binding of plasminogen to fibrin and thereby stabilizing the fibrin clot. The purpose of this review is to summarize the pathogenesis, clinical phenotype, approaches to diagnosis and treatment for these three major disorders of fibrinolysis.